2005
DOI: 10.1158/0008-5472.can-05-0718
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Regulates the Association between β-Catenin and Actinin-4

Abstract: The E-cadherin/catenin system acts as an invasion suppressor of epithelial malignancies. This invasion suppressive activity seems be mediated not only by the cell adhesive activity of E-cadherin but by other undetermined signaling pathways elicited by B-catenin. In fact, cancer cells that have infiltrated the stroma reduce the expression of E-cadherin and accumulate B-catenin. We attempted to identify the alternative partner proteins that make complexes with Bcatenin in the absence of E-cadherin. An f100-kDa p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 47 publications
6
108
0
2
Order By: Relevance
“…Also, the association of actinin-4 and b-catenin was suppressed by transfection with E-cadherin cDNA, but induced by interfering RNA for E-cadherin. 38 These findings appear compatible with the present Actinin-4 and ovarian cancer S Yamamoto et al data, and suggest that molecular and functional association occurs between actinin-4 and b-catenin in ovarian carcinomas.…”
Section: Actinin-4 and Ovarian Cancer S Yamamoto Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…Also, the association of actinin-4 and b-catenin was suppressed by transfection with E-cadherin cDNA, but induced by interfering RNA for E-cadherin. 38 These findings appear compatible with the present Actinin-4 and ovarian cancer S Yamamoto et al data, and suggest that molecular and functional association occurs between actinin-4 and b-catenin in ovarian carcinomas.…”
Section: Actinin-4 and Ovarian Cancer S Yamamoto Et Alsupporting
confidence: 89%
“…Of these, Hayashida et al 38 recently demonstrated that, in human colorectal cancer cells, actinin-4 recruits b-catenin into the actin-rich cytoplasmic portion when E-cadherin expression is decreased. Also, the association of actinin-4 and b-catenin was suppressed by transfection with E-cadherin cDNA, but induced by interfering RNA for E-cadherin.…”
Section: Actinin-4 and Ovarian Cancer S Yamamoto Et Almentioning
confidence: 99%
“…These epithelial-stromal transition spots might be one of the possible molecular therapeutic targets. E-cadherin is found to be involved in the regulation of β-catenin and other molecules in cell adhesion processes [40]. By using microarrays and transcriptional intervention, Kuphal and Behrens, described how E-cadherin affects the Wnt pathway in CRC [41].…”
Section: Discussionmentioning
confidence: 99%
“…7 Recently, it was demonstrated that high cytoplasmic expression of actinin-4, a modulator of the cytoskeleton, is predominantly observed in budding cells of colorectal carcinoma. 29 Furthermore, high levels of actinin-4 are associated with increased cell motility. 30 Although it remains elusive if there is a causal relation between cytoplasmic Ep-CAM and actinin-4 expression, it is tempting to speculate that both proteins are closely involved in tumor budding.…”
Section: Discussionmentioning
confidence: 99%